Self-Imaging Effect in Liquid-Filled Hollow-Core Capillary Waveguide for Sensing Applications - Huang, Yijian (Sensors (Basel), 2019)
A high sensitivity fiber-optic sensor based on self-imaging effect in a hollow-core capillary waveguide (HCCW) is presented for sensing applications. The sensor is composed of a section of HCCW fusion spliced between single mode fibers (SMFs). The self-imaging effect in the HCCW is investigated with different fiber lengths and arc-fusion parameters. By infiltrating the hollow core with index matching liquids, the peak wavelength of the proposed device shifts towards longer wavelengths. The temperature and refractive index (RI) responses of the sensor are studied systematically. When temperature is increased from 25 °C to 75 °C, the temperature sensitivity of the device can be improved significantly with the infiltrated structure, and reaches −0.49 nm/°C, compared with that of the un-filled device, which is 9.8 pm/°C. For the RI response, the liquid-filled structure achieves sensitivity of 12,005 nm/RIU in the range between 1.448 and 1.450, slightly higher than the 11,920 nm/RIU achieved by the un-filled one. The proposed sensor exhibits the advantages of simple structure, high sensitivity and low cost, which may find potential applications in physical and chemical sensing.